The Use of Digital Flipbooks to Teach Clean and Healthy Living Habits to Early Childhood - Nur Ainiyah; Dian Permatasari Kusuma Dayu; Munirah (Universitas Pendidikan Ganesha, 2025)
Early Childhood Education students are a digital native generation familiar with technological devices from an early age, but learning practices have not yet optimized the pedagogical use of digital media. Limited teacher competency in designing interactive media is one factor that hinders meaningful technology integration. This study aims to explore and test the feasibility of developing Digital Flipbook media as an interactive learning tool that combines text, images, animation, sound, and video to create a more contextual and engaging learning experience. This research is a developmental research by adapting the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects involved early childhood learners and validators consisting of material experts and media experts. Data were collected through observation and validation sheets based on product feasibility assessment instruments. Data analysis was carried out using descriptive statistics and inter-rater agreement tests to ensure the consistency of the validation results. The results showed that Digital Flipbook was categorized as very feasible and consistent according to expert assessments. The conclusion of this study confirms that Digital Flipbook media has the potential to increase early childhood learning engagement and motivation, and has implications for strengthening technology-based learning practices that are more interactive, reflective, and in accordance with children's developmental characteristics.